Is sustainable intensification possible in smallholder crop production systems in semi-arid West Africa? The case of the Red Volta and Black Volta basins in Northern Ghana - Ansah, Prince (Department of Environmental and Geographical Science, 2024)
Food systems experts consider Sustainable Intensification (SI) a key concept to tackle the increasing global and regional food demand, particularly in semi-arid West Africa, which is prone to socioeconomic and biophysical challenges. In Ghana, crop production varies across semi-arid systems, particularly between the Red Volta and Black Volta basins. Given this context, the study assessed and compared the factors contributing to crop productivity differences between and within the RVB and the BVB and explored how these factors contribute to achieving SI goals of productivity, resilience, efficiency, and equity. This study applies an integrated SI framework and case study approach in these basins, using mixed methods: 200 household surveys, six in-depth interviews, three focus group discussions, five key informant interviews, and two workshops, with both random and purposive sampling. The results identified several important determinants of crop productivity that are relevant to SI. These included water/soil-related risks and strategies, access to agricultural resources, demographic characteristics, institutional collaboration, and household production needs. These determinants, which differ in importance within each basin, impact the achievement of SI goals. Farmers' perceptions of water/soil-related risks have a direct bearing on crop productivity across basins. Access to consistent resources was found to enhance yields, though an over-reliance on sporadic government support posed challenges especially in RVB. Demographic factors, notably age, gender, and education, emerged as significant determinants of farming practices and outcomes. Furthermore, the research emphasized the importance of robust inter-institutional collaboration in bolstering agricultural innovation and productivity. Notably, the choice of crops cultivated was influenced by a delicate balance between household consumption needs and market demands. The study underscores the need for local institutions to mitigate weak policies, limited resources, and poor knowledge transfer that could inhibit SI strategies implementation. The thesis concludes by recommending that national and local agriculture stakeholder should promote the SI concept as a guiding principle for improving existing farming systems through strengthening agriculture policies and facilitating innovations within smallholder crop production systems to enhance sustainable productivity in semi-arid Northern Ghana.